Study on the influence of the development of coordinative abilities on the forehand and backhand shots in table tennis for juniors IV - Moisescu, P. C.; Mocanu, M. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2017)
In order to achieve high performance in today`s table tennis, it is necessary to identify and use predominantly the most efficient means of training adapted to the age of the athletes subject to motor education, able to optimize the learning, fixing, consolidating and improving process for the execution of the technical-tactical elements in attack and defence, an aspect aimed at increasing performance. The present study was performed on 15 athletes aged 8-10 over a period of 6 months. The aim of this paper is to identify the opportunity to develop coordinative abilities in regard to increasing the efficiency of certain shots in this sport discipline. The objective of this research is to create a program able to optimize coordinative abilities, adapted to this discipline and age group, in order to fixate the counter game executed by forehand and backhand, by using the non-specific action systems in developing these motor skills. Premise: it is considered that at the present time there is no clear opinion on the direction mentioned above and our experimental research may improve performance and supplement the existing specialized literature. Methods used: pedagogical observation, the statistic-mathematical method, audio-video recording, the computerized graphical method. Discussion and conclusions: as a result of the experimental research, it was found that, in point of the values resulting from the statistic-mathematical analysis, as well as from pedagogical observation, the game of the athletes pertaining to the experimental group has improved during training sessions and competitions, thus proving that the direction proposed is a sure way to performance.